2012
DOI: 10.1021/ja3054942
|View full text |Cite
|
Sign up to set email alerts
|

Unraveling the Mechanisms of Nonradiative Deactivation in Model Peptides Following Photoexcitation of a Phenylalanine Residue

Abstract: The mechanisms of nonradiative deactivation of a phenylalanine residue after near-UV photoexcitation have been investigated in an isolated peptide chain model (N-acetylphenylalaninylamide, NAPA) both experimentally and theoretically. Lifetime measurements at the origin of the first ππ* state of jet-cooled NAPA molecules have shown that (i) among the three most stable conformers of the molecule, the folded conformer NAPA B is ∼50-times shorter lived than the extended major conformer NAPA A and (ii) this lifetim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
75
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 68 publications
(77 citation statements)
references
References 94 publications
2
75
0
Order By: Relevance
“…Only a few experimental studies suggest that the excited-state lifetime could be much shorter than the radiative lifetime. Thus conformer-dependent lifetimes in the 1-80 ns range have been reported at the origin of the first ππ* transition of isolated natural Phe [75,91] as well as of a more biologically relevant capped amino-acid [110,115,200], for which quantum chemical calculations have shown that peptide bond nπ* states are responsible for the lifetime shortening observed. Still shorter (sub-nanosecond) lifetimes are out of reach of the techniques employed, but are suspected to occur in the hydrates of capped Phe [200], suggesting that detection by ns-UV excitation might become a concern.…”
Section: Photophysics Of Aromatic Residues In Model Peptidesmentioning
confidence: 82%
See 1 more Smart Citation
“…Only a few experimental studies suggest that the excited-state lifetime could be much shorter than the radiative lifetime. Thus conformer-dependent lifetimes in the 1-80 ns range have been reported at the origin of the first ππ* transition of isolated natural Phe [75,91] as well as of a more biologically relevant capped amino-acid [110,115,200], for which quantum chemical calculations have shown that peptide bond nπ* states are responsible for the lifetime shortening observed. Still shorter (sub-nanosecond) lifetimes are out of reach of the techniques employed, but are suspected to occur in the hydrates of capped Phe [200], suggesting that detection by ns-UV excitation might become a concern.…”
Section: Photophysics Of Aromatic Residues In Model Peptidesmentioning
confidence: 82%
“…Such a situation has not yet been revealed on peptides, only lifetimes strongly varying with conformation in the nanosecond regime having been encountered. These measurements are scarce and are limited to Phe-based peptides [75,91,110,115] and Tyr [56]. In a few peptiderelated compounds, presenting a phenyl chromophore and an amide group, short monomer lifetimes are suspected [18].…”
Section: Lessons From the Confrontation mentioning
confidence: 99%
“…Highly efficient non-radiative relaxation pathways for excited states of hydrogen-bonded peptide conformers were recently proposed by Mališ et al [23] A folded conformer of N-acetylphenylalaninylamide (NAPA), containing two intramolecular H-bonds (one of the NH•••O type, the other an NH-π bond between the N Phe H bond and the phenyl ring), was revealed by R2PI experiments to have a short excited-state lifetime (~1.5 ns). This explained its absence from earlier laser-induced fluorescence studies.…”
Section: Resultsmentioning
confidence: 99%
“…In the former report, [22] excited state dynamics of each conformer of Phe were experimentally investigated and it was demonstrated that S 1 state lifetimes differ among conformers. Furthermore, for the peptides, it has been reported that the excited state dynamics are strongly affected by the conformations [38,39]. Thus it will be interesting to compare the photophysical properties such as lifetime between similar conformers of HPhe and Phe.…”
Section: Discussionmentioning
confidence: 99%